Levels of pain assessment tools for pediatric dental patients: a narrative review - Nagarwal, Priya; Rana, Vivek; Srivastava, Nikhil; Kaushik, Noopur (International Journal Of Community Medicine And Public Health, 2022)
Pain is defined as an unpleasant sensory and emotional experience associated with actual and potential tissue damage. Pain perception in children causes a number of changes in their emotional state. It can lead to emotions like fear, anxiety, sadness and might have an impact on day-to-day activities. Due to the lack of cognitive development young children are unable to express their pain verbally. Pain assessment can be carried out by using various approaches, such as self-reporting pain assessment tools, behavioural pain assessment tools and by assessment of various physiologic parameters. The process of pain evaluation for a child is strenuous as they have limited cognitive sophistication to describe their painful experiences during any disease process. Out of all the scales discussed, Wong-Bakers facial pain rating scale (WB-FPS) is considered the best as it is simple to use for the operator and can be easily reproduced and can be used in children as young as 3 years of age.